Newly Qualified Teachers and Inclusion in Higher Education: Policy, practice and preparation. - Colum, Miriam (JHEPALS, 2021)
Higher education policy in Ireland ensures that student teachers are prepared for all aspects of life as a future educator and this is underpinned by documents such the Policy on the Continuum of Teacher Education (Teaching Council, 2011a); Criteria and Guidelines for Programme Providers, (Teaching Council, 2011b); and, Guidelines on School Placement (Teaching Council, 2013) and more recently ‘Céim: Standards for Initial Teacher Education’ (Teaching Council, 2020). Considering these policies, this paper draws on research for an undergraduate dissertation on the preparedness of newly qualified teachers (NQTs) for inclusive special education classrooms. The methodology employed is documentary research in the first instance, followed by the lived experience of one of the authors who is currently in her first year as an NQT. Her role is spread across five schools as both a mainstream and a special education teacher. This narrative reflects literature, highlighting commonalities of lack of confidence in knowledge and skills pertaining to aspects of special education, uncertainty around the practicalities of inclusion and general nervousness as a newly qualified teacher. It also highlights the supportive structures for NQTs such as leadership, collaboration and professional conversations for these teachers as they navigate busy and demanding school and classroom settings. Notwithstanding deep-rooted uncertainty in skills and knowledge, there is an overall sense of positivity and a feeling of optimism as an inclusive educator in the teaching profession.
Keywords: Newly Qualified Teachers; Inclusion; Special Education; Policy in teaching; Educational policy; Practice of Inclusion in Schools; Preparation for Newly Qualified Teachers; NQT; Teacher education; Inclusive education; Higher Education; Special education; Education--Ireland